2014
DOI: 10.1016/j.disc.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

On the girth of the bipartite graph D(k,q)

Abstract: In this paper, we deal with a generalization Γ(Ω, q) of the bipartite graphs D(k, q) proposed by Lazebnik and Ustimenko, where Ω is a set of binary sequences that are adopted to index the entries of the vertices. A few sufficient conditions on Ω for Γ(Ω, q) to admit a variety of automorphisms are proposed. A sufficient condition for Γ(Ω, q) to be edge-transitive is proposed further. A lower bound of the number of the connected components of Γ(Ω, q) is given by showing some invariants for the components. For Γ(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The study on European perch (Dicentrarchus labrax L.) also showed that VD 3 increased the phagocytosis of white blood cells in the head kidney, while inhibited the expression of il-1β in the head kidney and intestinal tract (49) . Furthermore, the addition of dietary VD 3 inhibited the upregulation of pro-inflammatory cytokines induced by bacterial infection in yellow catfish (25) and Jian carp (Cyprinus carpio var.jian) (47) . Consistently, our results demonstrated that the gene expression of the pro-inflammatory cytokines, including il-1β, il-8, il-6 and tnf-α, was significantly lower in the liver and gut of the turbots in 400 IU group (Figure 4A-B),…”
Section: Discussionmentioning
confidence: 99%
“…The study on European perch (Dicentrarchus labrax L.) also showed that VD 3 increased the phagocytosis of white blood cells in the head kidney, while inhibited the expression of il-1β in the head kidney and intestinal tract (49) . Furthermore, the addition of dietary VD 3 inhibited the upregulation of pro-inflammatory cytokines induced by bacterial infection in yellow catfish (25) and Jian carp (Cyprinus carpio var.jian) (47) . Consistently, our results demonstrated that the gene expression of the pro-inflammatory cytokines, including il-1β, il-8, il-6 and tnf-α, was significantly lower in the liver and gut of the turbots in 400 IU group (Figure 4A-B),…”
Section: Discussionmentioning
confidence: 99%